Proposal of Action Plan for the Costa Rican Red Cross Auxiliary Committee of San Vito to Reach Carbon-Neutrality - Gómez-Céspedes, Jairo (2016)
In the context of the Costa Rica's carbon neutrality strategy, in this study an inventory of greenhouse gases (GHG) has been carried out, requirements were analyzed, and necessary recommendations were given for the Red Cross auxiliary committee of San Vito de Coto Brus to diagnose their possibility of becoming a carbon-neutral organization. Information on C-Neutral certification options at the national level was collected. INTE/ISO 14064:2006 and INTE/ISO 12-01-06:2011 were taken as a reference to carry out the GHG inventory, and to give the recommendations to implement C-Neutral management system respectively. 2014 was the year of the committee operations taken as a reference for the inventory. As the result of the inventory, the sources of GHG sources were identified and their emissions quantified, in accordance with national and international factors; 77.4 tons of total emissions of carbon equivalent (tCOe) were quantified, coming mainly from sources of hydrocarbons combustion (fleet vehicle). Also a template with stoichiometric equations for future GHG measurements and a matrix of fulfillment of requirements and recommendations were designed for the eventual certification of the C-neutral system, in order to be implemented in any of the Red Cross committees in Costa Rica.